2009
DOI: 10.1111/j.1537-2995.2009.02269.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of human herpesvirus 8 (HHV‐8) antibody in patients transfused with HHV‐8–seropositive blood

Abstract: The source of transient antibody in patients who received transfusions was determined to be the transfused blood. Donors with higher HHV-8 antibody titers may have been less likely to have infectious virus in the blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…A previous study on HHV8 transmission has shown that transmission of HHV8 via blood is inefficient [25]. In fact passive transfer of HHV8 antibody was even suggested to have a protective effect against HHV8 transmission [26]. In our study, no association between sexual behaviour, including multiple sex patterns and condom use, and HHV8‐positive status was observed.…”
Section: Discussioncontrasting
confidence: 60%
“…A previous study on HHV8 transmission has shown that transmission of HHV8 via blood is inefficient [25]. In fact passive transfer of HHV8 antibody was even suggested to have a protective effect against HHV8 transmission [26]. In our study, no association between sexual behaviour, including multiple sex patterns and condom use, and HHV8‐positive status was observed.…”
Section: Discussioncontrasting
confidence: 60%
“…Storing blood for several hours or days would also likely reduce the risk of transmission since we have observed that KSHV DNA detection is frequently reduced or abolished if blood from KSHV infected subjects is stored overnight before DNA extraction [Whitby and Uldrick, unpublished observations] These measures seem to be preferable to the introduction of screening blood or blood products for KSHV antibodies given the limitations of currently available assays[47] [48]. Such screening may even be counter-productive since a recent report demonstrated that transmission of KSHV occurred less frequently when donors had higher levels of antibodies[49]. The relationship between antibody titre, KSHV viral load and transmissibility of KSHV is clearly complex[50; 51]and is an area that warrants further study.…”
Section: Kshv Transmissionmentioning
confidence: 99%
“…Recipient 2027, negative for IgG to HHV‐8 before transfusion, seroconverted after receiving an antibody and DNA positive whole blood transfusion. As demonstrated by Fowlkes and coworkers, 16 passive antibodies are detected immediately after transfusion with a relatively high titer and become undetectable in approximately 3 weeks. Immune response becomes detectable 4 to 10 weeks posttransfusion and is high titer.…”
Section: Discussionmentioning
confidence: 79%